Clinical Features and Surgical Strategies of Distal Radius Posttraumatic Deformity - Ning Zhang; Jiahu Fang (Emergency Medicine International)
Objective. To investigate the clinical features and surgical strategies of distal radius posttraumatic deformity. Methods. A retrospective analysis was performed on the data of 30 patients with distal radius posttraumatic deformity treated by osteotomy and orthopedic surgery in the department of orthopedics, the First Affiliated Hospital of Nanjing Medical University, from February 2016 to November 2018. All the patients underwent preoperative anterior and lateral X-ray plain scanning of bilateral wrist joints, showing different degrees of radius shortening, inferior ulnar and radial mismatch, palmar angle, and ulnar deviation angle, among which 11 patients had an uneven joint surface. After a full evaluation, osteotomy and orthopedic surgery were performed to restore the original anatomical structure, plaster fixation was performed for two weeks after surgery, and regular outpatient follow-up was conducted. The function of the wrist was evaluated by the MMWS (wrist joint improvement) scoring scale before and after surgery, and the changes in the wrist joint-related treatment parameters were evaluated according to X-ray. Results. All 30 patients had no neurological symptoms after surgery, and all wounds healed within the first stage. All patients were followed up for 6–12 months, with an average healing time of 3.5 months. There was no reduction loss, internal fixation loosening, or fracture in the regular postoperative review. Postoperative MMWS (wrist joint improvement) score scale data were significantly higher than those before surgery, and there were differences between groups (P<0.05). Postoperative treatment parameters of wrist joints such as palmar inclination angle, ulnar deviation angle, radius height, and lower ulnar and radial matching were significantly improved, and there were differences between groups (P<0.05). Conclusions. The patients with distal radius posttraumatic deformity have the clinical characteristics of shortening of radius, mismatch of lower ulnar and radius, an abnormal inclination of palm, and ulnar declination. For patients with distal radius posttraumatic deformity, osteotomy and orthopedic surgery can effectively improve wrist function and improve patients’ quality of life, which is worthy of clinical reference.